METHODOLOGICAL BASIS FOR EVALUATING THE INVESTMENT POTENTIAL OF FOOD INDUSTRY ENTERPRISES - Ismailov Akmal Maksudovich (American Journals, 2024)
The article examines one of the main economic categories - investment potential. In particular, the essence of the concept of food industry enterprises is revealed and the need for a comprehensive review from the point of view of food industry enterprises carrying out investment activities is shown. The investment potential of food industry enterprises is defined and the factors forming it are formed.
Keywords: Food industry, investment potential, investment resources, financial potential, production potential, labor potential, innovation potential, marketing potential, potential potential, management potential.